4 Del. Laws 522 (1812) - (:unkn) unknown (My University, 1812)
An Act to Prevent the Discharging of Fire-Arms Within the Towns and Villages, and Other Public Places Within this State, and for Other Purposes. §1: Prohibited the discharge of any gun, ordinance, musket, fowling piece, fuse, or pistol in any town or village. When town limits cannot be ascertained, not within one quarter mile of the centre of such town or village, the greens, streets, alleys or lanes of any town or village.
Keywords: DISCHARGE